Quality of government and living standards : adjusting for the efficiency of public spending - Grigoli, Francesco; Ley, Eduardo (IMF working paper, 2012)
It is generally acknowledged that the government's output is difficult to define and its value is hard to measure. The practical solution, adopted by national accounts systems, is to equate output to input costs. However, several studies estimate significant inefficiencies in government activities (i.e., same output could be achieved with less inputs), implying that inputs are not a good approximation for outputs. If taken seriously, the next logical step is to purge from GDP the fraction of government inputs that is wasted. As differences in the quality of the public sector have a direct impa.